Impact of suboptimal land on shallot plant growth - Hawayanti, Erni; Ibrahim, Jabal Tarik; Sutanto, Adi; Muchsiri, Muchtaruddin (Environmental and Agriculture Management, 2024)
This research aims to review the impact of suboptimal land on the growth of shallot plants by integrating the latest findings from related scientific studies. This review includes an evaluation of shallot plant growth parameters that are influenced by suboptimal land conditions, as well as land management strategies that can be used to increase plant productivity. Through this comprehensive approach, it is hoped that this review will provide in-depth insight into the complexity of interactions between shallot plants and their growing environment.